Macroplastic transfer dynamics in the Loire estuary: Similarities and specificities with macrotidal estuaries. (September 2022) - Ledieu, L.; Tramoy, R.; Mabilais, D.; Ricordel, S.; Verdier, L.; Tassin, B.; Gasperi, J.
Abstract: The quantification of macroplastic fluxes transferred by rivers toward the pelagic environment requires a better understanding of macrodebris transfer processes in estuarine environments. Following the strategy adopted in the Seine estuary, this study aims to characterize macroplastic trajectories in the Loire estuary. Between January 2020 and July 2021, 35 trajectories were monitored using plastic bottles equipped with GPS-trackers. With total travelled distances between 100 m and 103.6 km, trajectories show great spatiotemporal variability. The various forcing factors (macroplastic buoyancy, estuaries tidal and hydrometeorological conditions, geomorphology and vegetation) lead to chaotic trajectories, preventing accurate predictions in macroplastic transfer and storage/remobilization dynamics. In the Loire estuary like in the Seine one, no tracked bottle reached the Atlantic Ocean. It confirms that macrotidal estuaries under temperate climates constitute accumulation zones and slow pathways for macroplastics, but raises question on the real fluxes transferred from continental areas to oceans. Highlights: Macroplastics transfer dynamics have a myriad of forcing factors. Macroplastics have chaotic and stepwise trajectories within macrotidal estuaries. Macrotidal estuaries are slow pathway and accumulation zones for macroplastics. The estuarine geomorphology lead to site-specific dynamics and accumulation zones.